Effects of gamma irradiation on the degradation of silicone rubber by steam exposure. Issue 2 (1st February 2021) - Ito, Seitaro; Miyazaki, Yu; Hirai, Naoshi; Ohki, Yoshimichi
ABSTRACT: Silicone rubber (SiR) is an important electrical insulating material for safety-related cables in nuclear power plants. This means that SiR must withstand the irradiation of gamma rays and the exposure to high-temperature steam. However, SiR is vulnerable to hydrolysis. Therefore, for the purpose of clarifying the behavior of SiR in such environments, sheets of SiR were exposed to steam at 171 or 200°C with and without pre-irradiation of gamma rays. As a result, it has become clear that SiR can withstand the exposure to high-temperature steam more robustly if it was irradiated by gamma rays to a proper dose in advance.